Epidemiological landscape and genetic prospects for marker-assisted selection in Kazakh sheep - Orkara, Shynggys; Khamzina, Aigerim; Sandybayev, Nurlan; Sattarova, Rano; Davletova, Ainur; Khamzin, Kadyrzhan; Pokharel, Kisun; Ibragimov, Primkul; Burambayeva, Nadezhda; Smagulov, Darkhan (Frontiers in Veterinary Science, 2025)
This comprehensive review examines the current epidemiological landscape, genetic resistance mechanisms, and control strategies for major sheep diseases in Kazakhstan. The study systematically analyzes three primary disease categories: parasitic infestations (including echinococcosis, fascioliasis, gastrointestinal strongylatosis, and protozoan infections), infectious diseases (foot rot, scrapie, Maedi-Visna, pasteurellosis, brucellosis), and hereditary disorders. Our analysis revealed significant regional variations in disease prevalence, with southern and western regions of Kazakhstan exhibiting higher parasitic burdens, particularly for echinococcosis and fascioliasis. Recent molecular studies have identified promising genetic markers associated with disease resistance, notably polymorphisms in the MHC complex (particularly DRB1 and DQB1 loci) conferring protection against parasitic infections and the PRNP gene variants influencing scrapie susceptibility. Current disease control approaches in Kazakhstan predominantly rely on chemical treatments and vaccination programs, while genetic selection for disease resistance remains underutilized despite its demonstrated efficacy in international breeding programs. The integration of marker-assisted selection and genomic approaches represents a promising strategy for enhancing disease resistance while maintaining productivity in Kazakhstani sheep breeds. This review highlights critical knowledge gaps, particularly regarding the molecular epidemiology of hereditary disorders as a markers of ecological plasticity and the genetic basis of resistance to infectious diseases in local breeds, emphasizing the need for comprehensive surveillance programs and targeted research to develop sustainable disease management strategies for Kazakhstan’s sheep industry.